Exploring the perspectives of health service providers on mental health policy and interventions for school children in the Western Cape, South Africa - Mgoqi, Khusela (Department of Public Health and Family Medicine, 2022)
Background: Mental health is recognised as a critical public health challenge globally, yet child and adolescent mental health receive low priority, particularly in low- and middle-income countries. Children and adolescents spend a significant proportion of their lives in school, suggesting that educational settings are potentially important environments where child and adolescent mental health (CAMH) can be strengthened to improve early identification and treatment. This study explored the perspectives of key service providers on needs, barriers and facilitators of child and adolescent mental health services (CAMHS) in schools in the Western Cape province of South Africa. Methods: This study employed an exploratory qualitative approach. In-depth individual interviews were conducted by one of the authors (SM), and the first author (KM) conducted a thematic analysis on the interview data. Results: There were nine interviewees selected who were diverse health service providers involved in child and adolescent health which included school doctors, school nurses, psychiatrists, occupational therapist, clinical nurse and mental health nurse. Thematic findings were grouped under: a) perceived needs, b) barriers and c) facilitators. The need to improve intersectoral collaboration, following a referral pathway, a strong multidisciplinary team (MDT) and integration of services were all identified important in the delivery of CAMHS. The neglect of CAMHS in both education and health sectors and limited resources were identified as barriers. Facilitators included intersectoral collaboration, task shifting from nurses and doctors to community health workers, and committed health workers. Conclusion: CAMHS receives very low priority in comparison to other health issues such as HIV/TB in South Africa. There is an urgent need to address CAMHS in South Africa, and the school setting is an important site of intervention. Intersectoral collaboration, task-shifting, continuous training of teachers and health professionals are potential strategies that could be used to strengthen access to CAMHS in education sector and have integrated services in the Western Cape Province.